Prediction of four-days Soaked California Bearing Ratio (CBR) Values from Soil Index Properties - Ambrose, Pascal; Rimoy, Siya (Tanzania Journal of Engineering and Technology, 2021)
California Bearing Ratio (CBR) laboratory testing is the conventional method for determining soaked strengths of pavement subgrades. The test requires careful preparation of soil samples followed by four days of water soaking before penetrating the samples using a standard plunger at prescribed rates to set depths. When the number of samples becomes large the determination of soaked CBR values becomes cumbersome as the test is laborious and time consuming. This study aimed at establishing an alternative way of determining soaked CBR by developing a model that would be used for estimating soaked CBR of fine- and coarse- grained soils without performing the CBR test. This has been achieved by correlating CBR values compacted at 95% Maximum Dry Density (MDD) with the soil index properties. The results show that soaked CBR values of fine-grained soils significantly correlate with specific gravity of soil (GS), Plasticity index (PI) and the grading modulus (GM) of the soil that yields a degree of determination of R2 = 0.91 and for coarse grained (A-2 type) soil, the soaked CBR values significantly correlate with specific gravity of soil and percentage of fines passing 0.075mm sieve size that yields a degree of determination of R2= 0.94. Keywords: Four-days soaked California Bearing Ratio (CBR), Soil Index Properties, Subgrade.